2009
DOI: 10.1007/s10517-009-0493-3
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Changes in Rats Induced by a Dipeptidyl Peptidase IV Inhibitor Methionyl-2(S)-Cyanopyrrolidine: Experimental Model of Anxiety-Depression Disorder

Abstract: Administration of a synthetic dipeptidyl peptidase IV inhibitor methionyl-2(S)-cyanopyrrolidine (1 mg/kg) to rats during the early postnatal period was followed by the development of behavioral changes in young and adult animals. The degree of anxiety in the elevated plus maze increased in treated rats at the age of 1-2 months. Depressive behavior in the forced swimming test was typical of animals aging 2-3 months. Diazepam reduced the severity of anxiety in treated rats. Melipramine had a normalizing effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…Previously, we have shown that postnatal methionyl-2(S)-cyano-pyrrolidine, a synthetic non-competitive irreversible inhibitor of DPP-IV, causes anxiety-and depression-related behaviors in adolescent and adult rats (from the first to the seventh month) [29] [47]. In the present study, we have demonstrated that rat pups exposed to DPP-IV inhibitors with different mechanisms of action in the early postnatal period might develop persistent behavioral disorders.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previously, we have shown that postnatal methionyl-2(S)-cyano-pyrrolidine, a synthetic non-competitive irreversible inhibitor of DPP-IV, causes anxiety-and depression-related behaviors in adolescent and adult rats (from the first to the seventh month) [29] [47]. In the present study, we have demonstrated that rat pups exposed to DPP-IV inhibitors with different mechanisms of action in the early postnatal period might develop persistent behavioral disorders.…”
Section: Discussionsupporting
confidence: 57%
“…By comparing the appearance and maintenance of the behavioral disorders in the diprotin A-and sitagliptintreated, we concluded that, in this study, diprotin A caused more pronounced and long-term consequences, which are comparable to the effects of methionyl-2(S)-cyano-pyrrolidine [29]. The latter inhibitor was used at a dose of 1 mg per kg at the same time points with an approximately equimolar amount (MW 199.27).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In the present study, dpp4 gene expression was increased in the striatum in rats after neonatal exposure to sitagliptin, and prep gene expression was increased in the same structure in rats after neonatal exposure to diprotin A. The results of the study confirm the participation of the proline-specific peptidases DPP-IV and PREP in the pathogenesis of emotional and motivational disorders, as discussed in our previous work [27-29]. …”
Section: Discussionsupporting
confidence: 90%
“…In our studies, equimolar doses of the synthetic noncompetitive irreversible inhibitor of DPP-IV, methionyl-2(S)-cyanopyrrolidine, and selective competitive DPP-IV inhibitors, sitagliptin and tripeptide diprotin A, which is the DPP-IV substrate, administered in rats on PND 5–18 led to the development of an anxiety-depression-like state with increased aggression manifested in the social contact test, which was conducted after 2–3 days of isolation [27-29]. The data indicate that DPP-IV could participate in the genesis of emotional and motivational disorders, but it does not describe possible mechanisms for such participation.…”
Section: Introductionmentioning
confidence: 99%